The Representation of Muslims in Rudyard Kipling’s Short Stories: A Postcolonial Perspective - M. Mugijatna (Al-Jami'ah Research Centre, 2014)
This article studies Rudyard Kipling’s four short stories, “Wee Willie Winkie”, “The Recrudescence of Imray”, “The Story of Muhammad Din”, and “Without Benefit of Clergy”. The purposes of this research are to describe the representation of Muslims in the four short stories and to describe how the representation of Muslims in the four short stories represents British colonization in India. In this paper, I employs textual study methodology using narrative analysis, binary-opposition analysis, and metaphorical iconicity analysis. The conclusion is that the representation of Muslims in the four short stories ranges from perceiving Muslims as bed men living in hills and forest to perceiving Muslims as the slaves of the British. In all the representations, the British is not presented as an oppressor, instead as a benevolent master. It is a metaphor of Kipling’s firm belief that the British were helping to civilize and educate a previously “savage” people. It disregards the fact that British colonization over India had ruined Islamic empire in India under Mogul Court sovereignty and ruined Indian economy and society organization.[Penelitian ini mengkaji empat cerita pendek Rudyard Kipling, “Wee Willie Winkie”, “The Recrudescence of Imray”, “The Story of Muhammad Din”, dan “Without Benefit of Clergy”. Adapun tujuan dari penelitian ini adalah mendeskripsikan representasi Muslim dalam empat cerita pendek tersebut dan mendeskripsikan bagaimana gambaran tersebut merepresentasikan kolonisasi Inggris atas India. Metode yang digunakan adalah metodologi kajian tekstual dengan analisis naratif, analisis oposisi-biner, dan analisis ikonositas metaforis. Kesimpulannya adalah bahwa representasi Muslim dalam empat cerita pendek tersebut merentang mulai dari muslim sebagai orang-orang jahat yang hidup di gunung dan hutan hingga sebagai budak orang Inggris. Dalam represestasi itu orang Inggris tidak pernah digambarkan sebagai penindas. Representasi ini merupakan metafora kepercayaan Rudyard Kipling bahwa kehadiran Inggris di India adalah untuk mengadabkan dan mendidik orang India yang semula liar. Representasi ini mengabaikan kenyataan bahwa kehadiran Inggris di India telah menghancurkan imperium Islam di India di bawah kedaulatan Istana Mogul dan meruntuhkan ekonomi dan susunan masyarakat India.]